2000
DOI: 10.1046/j.1365-2273.2000.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of otitis media with effusion in British pre-school children: a guide for treatment

Abstract: Data on the prevalence of otitis media with effusion (OME) as shown by serial tympanometry is presented for young children during the first 5 years of life. The children were participants in the Avon Longitudinal Study of Pregnancy and Childhood (ALSPAC); a randomly selected 10% (n = 1400) of whom were selected for examination at ages 8, 12, 18, 25, 31, 37, 43, 49 and 61 months. Whilst sex had no effect, there was a decrease in prevalence of OME with increasing age. There was a marked seasonal effect on the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
2
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 18 publications
2
50
2
7
Order By: Relevance
“…However, this is equally probable for the children in the control groups. The incidence of OME in children aged five to six is about 15-17%, but most of these children are only affected for shorter periods (Midgley, Dewey, Pryce, and Maw, 2000;Williamson, Dunleavey, Bain, and Robinson, 1994) and there are no studies showing that shorter periods of OME influence speech development.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is equally probable for the children in the control groups. The incidence of OME in children aged five to six is about 15-17%, but most of these children are only affected for shorter periods (Midgley, Dewey, Pryce, and Maw, 2000;Williamson, Dunleavey, Bain, and Robinson, 1994) and there are no studies showing that shorter periods of OME influence speech development.…”
Section: Discussionmentioning
confidence: 99%
“…The point prevalence of OME is of the order of 15-25% in the 0-6-year-old age group, with peaks in the first year of life and at school entry. [15][16][17] The period prevalence across that age range may be as high as 80%. Most cases resolve within 2-3 months.…”
Section: The Nature Of Childhood Hearing Impairmentmentioning
confidence: 99%
“…These included the Waltham Forest study reported in Chapter 3, published prevalence surveys, published surveys of clinical practice, published treatment guidelines, reviews and intervention studies. 12,17,[81][82][83] In most cases it was not possible to combine estimates from different studies into table distributions for these other events, so triangular distributions of mean or most likely estimates with minimum and maximum were used. …”
Section: Likelihood Of Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Na análise socioeconômica da amostra, não foi considerado o convívio com outras crianças, bem como a permanência em berçários ou creches, embora isso seja um fator de risco para a presença de secreção na orelha média, discutido na literatura.…”
Section: Resultsunclassified